Old enemies meet new friends for colon cancer prevention - Poutahidis, Theofilos (Oncoimmunology, 2015)
Our studies in mice have suggested that the immunological microenvironment of preneoplastic lesions could determine their fate toward neoplasia or regression. A role for gastrointestinal tract bacteria antigens in modulating cancer-related immune responses in the tumor micro- and macro-environment is emerging, thus opening new possibilities for colon cancer prevention.